2012
DOI: 10.1182/blood-2011-11-393827
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 is critical for the pathogenesis of a subset of MLL-AF9–rearranged AMLs

Abstract: The proto-oncogene EVI1 (ecotropic viral integration site-1), located on chromosome band 3q26, is aberrantly expressed in human acute myeloid leukemia (AML) with 3q26 rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 48 publications
5
77
0
Order By: Relevance
“…36 In a following study, Bindels et al showed that approximately 43% of all cases with MLL/KMT2A rearrangement are positive for EVI1 by real-time reverse transcription polymerase chain reaction, and EVI1 expression plays a critical role for the pathogenesis of a subset of AMLs with MLL-AF9 rearrangement. 37 Similar to patients with EVI1 gene rearrangements, EVI1 overexpression without 3q26.2/EVI1 translocation is also associated with poor prognosis in patients with AML. 38 In CML, Daghistani et al have shown that EVI1 overexpression is associated with imatinib resistance.…”
Section: Discussionmentioning
confidence: 97%
“…36 In a following study, Bindels et al showed that approximately 43% of all cases with MLL/KMT2A rearrangement are positive for EVI1 by real-time reverse transcription polymerase chain reaction, and EVI1 expression plays a critical role for the pathogenesis of a subset of AMLs with MLL-AF9 rearrangement. 37 Similar to patients with EVI1 gene rearrangements, EVI1 overexpression without 3q26.2/EVI1 translocation is also associated with poor prognosis in patients with AML. 38 In CML, Daghistani et al have shown that EVI1 overexpression is associated with imatinib resistance.…”
Section: Discussionmentioning
confidence: 97%
“…2,6,14,15,[28][29][30] Animal models demonstrate that forced overexpression of EVI1 results in myeloid hyperproliferation, downregulation of genes related to myeloid differentiation, and cause a fatal disorder resembling human MDS. 20,21,30,31 In humans, rare cases have been reported of myelodysplasia with monosomy 7 related to overexpression of EVI1 caused by retroviral insertional activation during gene therapy. 22 Thus, the biological importance of the inv(3)/t(3;3) in the development of myeloid malignancy is known and can be used as a unifying theme for considering AML and MDS with this abnormality as a discrete entity.…”
Section: Discussionmentioning
confidence: 99%
“…29 Cells were crosslinked at room temperature for 10 minutes with 1% formaldehyde and sonicated to shear the chromatin. Immunoprecipitation of crosslinked chromatin was performed overnight at 4°C with antibodies directed against the histone mark H3K27ac, the coactivator p300, and TFs including RUNX1, LMO2, PU.1, ERG, TAL1, and SCL, or an equal amount of isotype immunoglobulin G (IgG) as background control (http://149.171.101.136/python/ BloodChIP/search.html).…”
Section: Chip Sequencingmentioning
confidence: 99%